2022
DOI: 10.1002/advs.202104463
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive and Individual‐Centered Monitoring of Uric Acid for Precaution of Hyperuricemia via Optical Supramolecular Sensing

Abstract: Characterized by an excessively increased uric acid (UA) level in serum, hyperuricemia induces gout and also poses a great threat to renal and cardiovascular systems. It is urgent and meaningful to perform early warning by noninvasive diagnosis, thus conducing to blockage of disease aggravation. Here, guanidinocalix[5]arene (GC5A) is successfully identified from the self-built macrocyclic library to specifically monitor UA from urine by the indicator displacement assay. UA is strongly bound to GC5A at micromol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 77 publications
0
8
0
1
Order By: Relevance
“…Traditional diagnosis of hyperuricemia typically involves invasive blood collection, specialized instruments, and skilled hospital operators to measure the blood UA level. 47 In this study, the developed plasmonic biochips demonstrated the ability to sensitively, selectively, and noninvasively detect UA in artificial tears at concentrations within the physiological range. The achieved limit of detection for UA is lower than the average physiological level of UA in tears, indicating that the plasmonic biochips fabricated using the ZnO nanocages decorated with yolk–shell nanomaterials hold significant potential for sensitive sensing applications.…”
Section: Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Traditional diagnosis of hyperuricemia typically involves invasive blood collection, specialized instruments, and skilled hospital operators to measure the blood UA level. 47 In this study, the developed plasmonic biochips demonstrated the ability to sensitively, selectively, and noninvasively detect UA in artificial tears at concentrations within the physiological range. The achieved limit of detection for UA is lower than the average physiological level of UA in tears, indicating that the plasmonic biochips fabricated using the ZnO nanocages decorated with yolk–shell nanomaterials hold significant potential for sensitive sensing applications.…”
Section: Results and Discussionmentioning
confidence: 97%
“…Moreover, Raman intensities from 30 different regions across the yolk–shell nanomaterial-decorated ZnO nanocages with uric acid (200 μM) exposure show the reproducibility of the SERS substrate (Figure S14F). Traditional diagnosis of hyperuricemia typically involves invasive blood collection, specialized instruments, and skilled hospital operators to measure the blood UA level . In this study, the developed plasmonic biochips demonstrated the ability to sensitively, selectively, and noninvasively detect UA in artificial tears at concentrations within the physiological range.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Finally, the analysis of mice blood samples confirmed the potential of this sensing system for application in a practical diagnosis. We also detected various other bioactive molecules, such as trimethylamine N -oxide, uric acid, and biophosphonates, providing a convenient, rapid method of diagnosing conditions, such as atherosclerosis, thrombosis, and hyperuricemia. The reasonable design of macrocyclic receptors with excellent recognition properties ensures sensitive and selective detection and precise diagnosis.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] However, although with high sensitivity and excellent specificity, these methods are suffered from the complicated and laborious procedures, cost and time consumption, which is not conducive to home-based diagnosis and can impose a huge financial burden on families requiring long-time monitoring. [17] Consequently, it is urgent to develop a low-cost, simple, rapid, and sensitive method for PPA detection.…”
Section: Introductionmentioning
confidence: 99%